GREEN KNOWLEDGE MANAGEMENT TO IMPROVE GREEN COMPETENCE WITH GREEN MOTIVATION AS INTERVENING VARIABLE - Yenny Dwi Suharyani; Mafizatun Nurhayati (SEAN Institute, 2023)
Objectives: The purpose of this study is to find out knowledge management and motivation to improve managerial competence of a functional official of the Mining Inspector, an intermediate expert in provincial placements throughout Indonesia. Methodology: This review paper applies the keyword Green Competence (GC) and its relation to Green Knowledge Management (GKM), and Green Motivation (GM) from internet were published in 2017 or later. A preselect process conducted to figure out the suitable scientific paper related to Green Competence. Among hundreds of articles, we examine 24 from those which related to GC and its to GKM, and GM. Finding: This review paper revealed that there is a research gaps in this topic and this review paper also proposes a research framework for further research.Conclusion: A research conducted based on this review paper is important in order to enhance the competence of the inspectors who work in mining industry (mining inspector) in each province in Indonesia. Consequently, those mining inspector can carry out a technical supervision and environmental supervision towards Good Mining Practices (GMP).